Effects of instrument assisted soft tissue mobilisation in patients with chronic mechanical low back pain----A randomized control trial - Gul, Sameera; Bashir, Sana; Mushtaq Kayani, Nida; Sabir, Zoha; Qurat-Ul-Ain, Hafiza (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the effects of instrument-assisted soft tissue mobilisation compared to manual myofascial release in terms of managing pain, improving range of motion, and reducing disability in patients with chronic mechanical low back pain. Method: The randomised controlled trial was conducted from July 2022 to July 2023 at the Foundation University College of Physical Therapy and Gul’s Rehab Clinic, Rawalpindi, Pakistan, and comprised patients of either gender diagnosed with chronic mechanical low back pain. The patients were randomised into group A receiving manual myofascial release, and group B receiving instrument-assisted soft tissue mobilisation using long bar tool. The intervention lasted 9 sessions over 3 weeks. Data was analysed using SPSS 21. Results: Of the 50 participants 37(74%) were females and 13(26%) were males. The overall mean age was 25.1±6.9 years. There were 25(50%) patients in each group. Pain, lumbar range of motion, and lumbar disability improved significantly in both groups (p< 0.05). Intergroup difference was not significant (p>0.05). Conclusion: Manual myofascial release and instrument-assisted soft tissue mobilisation were equally effective in the treatment of chronic mechanical low back pain. RCT number: NCT05709925. https://classic.clinicaltrials.gov/ct2/results?cond=Low+Back+Pain&term=05709925&cntry=PK&state=&city=Rawalpindi&dist= Key Words: Chronic pain, Low back pain, Lumbar region, Myofascial release, Soft tissue injury.